Artificiell Insemination (AI) hos hund : en sammanställning över användandet av seminering inom hundaveln i Sverige under åren 1995-2004 - Stridh, Lena (SLU/Dept. of Clinical Sciences (until 231231), 2007)
The use of artificial insemination (A.I.) as an alternative to normal mating in dog breeding in Sweden are controlled by regulations from the Swedish Board of Agriculture and by ethical rules assigned by the Swedish Kennel Club. Only veterinarians, who have a specific certificate and are specially trained and educated, are allowed to perform inseminations in dogs. Each artificial insemination must be documented and reported to the Swedish Kennel Club (SKK) which, on the behalf of the Swedish Board of Agriculture, yearly presents statistics concerning the use of A.I. in Sweden. The objective of this study was to illustrate the use of artificial insemination in dog breeding in Sweden for the last decade, using the yearly reports from the Kennel Club during the period of 1995 to 2004.